(untitled) (Research, Society and Development, 2025)
Neurodegenerative diseases are characterized by their insidious onset and the severe complications they cause during their course, resulting in many disabilities and even death. This study aimed to evaluate the application of cerebrospinal fluid (CSF) laboratory analyses in the diagnosis and prognosis of multiple sclerosis and other demyelinating diseases. This research is a narrative literature review, which searched databases such as SciELO (Scientific Electronic Library Online), BVS (Virtual Health Library), Google Scholar, and PubMed for current academic articles that supported this study. The studies unanimously demonstrated the importance of CSF analysis in the diagnosis of neurodegenerative diseases such as multiple sclerosis, particularly in the assessment of intrathecal albumin synthesis and the application of the Reiber diagram to distinguish whether the elevation of immunoglobulins is due to passive diffusion due to blood-brain barrier damage or to intrathecal synthesis, as is characteristic of multiple sclerosis. Technological and scientific advances in CSF analysis make it a central tool in the diagnosis and prognosis of neurodegenerative diseases such as multiple sclerosis.